Tax Liability for Wage Theft - Pandya, Sachin S. (Columbia Journal of Tax Law, 2012)
This paper shows how, under existing tax law, illegal wage underpayment by an employer (sometimes called “wage theft”) may generate employer tax liability for unreported income or disallowed business expense deductions. Given that the tax authority needs information from the underpaid worker to prove such liability, the paper identifies two ways that a worker can transmit that information to a tax authority: becoming a tax informant, or bringing a qui tam action under a state false claims act. Finally, the paper discusses possible influences on the decision of the unpaid worker to inform on the employer to the tax authority, and considers the conditions under which a tax authority is likely to audit an employer based on such information. In so doing, the paper identifies a new approach to combating wage theft and an undiscovered implication of basic income tax law.